Estudio de prefactibilidad para la instalación de una planta para la elaboración de gomitas energizantes - Carbajal Silva, Marat (2023)
This paper explains the economic, technological and social viability of a plant implementation for the elaboration of energizing gummies based on a derivative of the coca leaf, the coca leaf atomized powder, and gently sweetened with organic panela. The idea of developing this product stems from the low diffusion and/or low use of the coca leaf and its derivatives in the daily or frequent diet in Peru, mainly in Lima, and there is significant potential to be exploited, due to the availability of land for its cultivation, no product has been massified, being the coca leaf or derivatives, the base of this. Therefore, this pre-feasibility study was carried out for the sale of 80-gram packages of gummies of 8 units, where it was determined thanks to the applied surveys that the intensity of purchase is 65.90% by our final consumer, and that this It is located mainly in Metropolitan Lima, and that its socioeconomic level can be A, B or C, also whose age varies between 15 and 60 years, and that is how it was determined that our demand for year 1 is 455,746 units. The analysis for the location of the plant showed, after using the Guerchet diagram, that the best place for its location is the constitutional province of Callao (industrial zone of Av. Argentina) and whose total area is 690 m2, and that production will be limited by the dehydrator. The production of these gummies will have exhaustive quality controls throughout the process, a HACCP plan will be implemented, and the good practices established by the competent entities will be complied with. Finally, the economic study was carried out to determine the viability of the project and the results of said study were the following: the total investment required for the project is S/ 4.804.994,81, being the most profitable to request a bank financing of almost 20% of the total investment. Likewise, the investment recovery period would be 3 years and 6 months; and a benefit of S/ 1,21 will be obtained for every S/ 1 invested, which proves that the project is economically viable.